A STUDY ON THE DIVERSITY OF MILLIPEDES (DIPLOPODA) IN VARIOUS HABITATS OF SATARA TAHSIL, WESTERN GHAT, MAHARASHTRA - Shaikh N. A.; Kengar S. B.; Atigre R. H; Abdar M. R (The Bioscan, 2025)
Diplopods are common in temperate, tropical, and subtropical plantation environments, as well as further atmospheres. Millipedes (Diplopoda) form a diverse group of invertebrates, playing an important role in distributing soil ecosystem facilities, though often poorly known. They act as decomposers, conserving soil erosion and nutrient cycling, and are among the greatest vital foliage litter creatures. Sympathetic soil invertebrate groups, together with the habitually essential millipedes, are vital (David 2015). The present study aims to know the diversity of millipedes in the exact habitations of Satara tahsil and to study how seasonal and edaphic structures affect their diversity. The present paper emphasizes the influence of these structures on millipede-type diversity, which originates from field studies conducted at three selected sites. These work efforts are focused on recording various millipede species found in the different habitats of Satara's study area. The study took place over a year, starting from 2023-24 and continuing to the present, focusing on the study area region in Satara. Our results showed that there are four genera present in the region, namely Anoplodesmus, Gyrodrepanum, Trigoniulus, and Xenobolus. The importance of millipedes in soil plays a direct role in its fertility. We distinguish various millipedes as indicators of ecological situations. The presence of millipedes is correlated with the content of organic matter and nutrient elements in the soil. The present assessment is attentive to their diversity, communication with fauna, food and feeding habits, and protection.